(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Rice is a principal crop cultivated across the coast of Bangladesh where plant spacing and nitrogen (N) level have distinct impingement on the rice production. But the favorable spacing along with appropriate N rate for this tidal coastal ecosystem has not decided yet. The study was escorted at Dumki upazila of Patuakhali district, Bangladesh during transplanted (T) Aus rice season of 2023 to find out optimum plant spacing and N fertilizer rates for rice in coastal ecosystem. Two factors Randomized complete Block Design was implemented in the study with three replications. The number of treatments was 12 which comprised of divergent levels of spacing (i.e. 20 cm ×15 cm, 25 cm ×15 cm, 20 cm ×20 cm, 30 cm ×15 cm, 25 cm × 20 cm, and 30 cm ×30 cm) and two different dosages of N (i.e. N rate of 50.4 kg ha-1 and 72 kg ha-1 that are equivalent to 70% and 100% of the recommended dosage of N, respectively). The findings of the study manifested that, although the yield assigning parameters like plant height, tillers hill-1, grains panicle-1 etc. increased with the increase of spacing, grain yield (t ha-1) was maximum (5.05 t ha-1) at closer spacing (i.e. 20 × 15 cm) and 50.4 kg N ha-1. At wider spacing, the number of tillers m-² was quiet less compared to closer spacing which basically results in low yield of rice crop. The 50.4 kg N ha-1 combined with 20 cm×15 cm spacing was the best treatment for Aus rice in the tidal coastal region of Bangladesh. J Bangladesh Agril Univ 23(3): 322–330, 2025